Clopidogrel use and smoking cessation result in lower coated-platelet levels after stroke. (17th February 2020) - Kirkpatrick, Angelia C.; Vincent, Andrea S.; Dale, George L.; Prodan, Calin I.
Abstract: Coated-platelets are a subset of highly procoagulant platelets elevated in patients with non-lacunar ischemic stroke and associated with stroke recurrence. Cross-sectional studies in controls have shown that smoking is associated with higher coated-platelet levels while chronic use of serotonin reuptake inhibitors (SSRIs), statins or aspirin is associated with lower coated-platelet levels. We now investigate if initiation of treatment with SSRIs, statins, clopidogrel, aspirin or oral anticoagulants and smoking cessation impacts coated-platelet levels at 90 days after ischemic stroke. Coated-platelet levels, reported as percent of cells converted to coated-platelets, were measured in 87 consecutive patients with stroke at baseline and repeated at 90 days. Repeated-measure ANOVA was used to determine if initiation of treatment with individual medications or smoking cessation impacted coated-platelet levels. Decreased coated-platelets levels at 90 days as compared to baseline were observed after initiation of treatment with clopidogrel (p = .0001, partial η 2 = 0.17) and smoking cessation (p = .014, partial η 2 = 0.10). Initiation of treatment with SSRIs, statins, aspirin or oral anticoagulants did not result in significant changes in coated-platelet potential. These novel longitudinal data suggest that clopidogrel therapy and smoking cessation attenuate coated-platelet potential at 90 days after ischemic stroke.